Kødets performativitet i kunst og teori - Heinrich, Falk (Academic Quarter | Akademisk kvarter, 2010)
Falk Heinrichs Kødets performativitet i kunst og teori (The performativity of flesh in art and theory). The article is an analysis of the function and meaning of living flesh in performative art and the connected art theory about performative aesthetics. The article meditates about flesh as materiality, action and concepts based on Marian Abramovic’s reenactment of various canonized ’body art’-works titled ’7 Easy Pieces’ re-performed in 2004. This ’academic’ meditation is supported by key concepts in the research discourse of performativity with the aim of distilling various aspects of flesh in artistic practice and theory.